2018
DOI: 10.35791/agrsosek.14.3.2018.21533
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Perempuan Pedagang Sayuran Terhadap Pendapatan Keluarga Di Pasar Bahu Manado

Abstract: The objectives of the research are: to find out (1) the contribution of income from trading vegetables to family income and (2) the outpouring of working hours of green vegetable traders at the Manado Bahu Market. This study used primary and secondary data. Primary data is colected through direct interviews with respondents based on the questionnaire. Secondary data were obtained from the relevant agencies, namely the Market Service Office Manado City and Sub-Office of Manado Bahu Market and literature review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
1
0
4
Order By: Relevance
“…The income of women traders is net income after deducting capital, user fees and transportation costs. This means that the role of women is very large in This research is in line with previous research by (Yulistien Djangaopa Y et al, 2018 ) with the title of the Contribution of women vegetable traders to family income at the Manado road shoulder market. Based on the research results, the average monthly donation of green vegetable traders to household income is 58.56% or IDR2.345.333.…”
Section: The Contribution Of Women Mobile Vegetable Traders To the Fa...supporting
confidence: 89%
See 1 more Smart Citation
“…The income of women traders is net income after deducting capital, user fees and transportation costs. This means that the role of women is very large in This research is in line with previous research by (Yulistien Djangaopa Y et al, 2018 ) with the title of the Contribution of women vegetable traders to family income at the Manado road shoulder market. Based on the research results, the average monthly donation of green vegetable traders to household income is 58.56% or IDR2.345.333.…”
Section: The Contribution Of Women Mobile Vegetable Traders To the Fa...supporting
confidence: 89%
“…They have been deemed inadequate, so homemakers tend to be pushed as mobile vegetable traders because, in general, homemakers have low levels of education and skills. (Yulistien Djangaopa Y et al, 2018 ) His research showed that the Contribution of the average monthly income of vegetable traders to household income was 58.56%, while the income of husbands was 22.47% and children 18.97%. According to (Sopamena, 2019), women play a role in coastal community households through important activities, namely: carrying out domestic activities plus as workers who contribute to household income.…”
Section: Introductionmentioning
confidence: 99%
“…Perempuan terlibat langsung dalam pemasaran sayuran karena mereka menganggap bahwa waktu yang dibutuhkan relatif kecil dan tenaga yang dibutuhkan tidak terlalu besar, sehingga perempuan lebih berperan dalam kegiatan tersebut. Selaras dengan pernyataan Djangaopa, Manginsela, & Baroleh (2018) bahwa perempuan terlibat langsung dalam pemasaran sayuran karena terdorong untuk memenuhi kebutuhan rumah tangga sehari-hari, berlangsung relatif mudah dan sederhana, tidak membutuhkan keterampilan khusus, serta modal yang digunakan relatif kecil.…”
Section: Peran Perempuan Dalam Aspek Pengambilan Keputusanunclassified
“…Menurut Pesik et al (2016), perempuan yang terlibat dalam pasar kerja atau bekerja sampingan di sektor non pertanian memiliki tujuan untuk mencari nafkah demi kelangsungan ekonomi rumah tangga. Berdasarkan hasil penelitian dari Djangaopa et al (2018), konsekuensi dari proporsi curahan kerja yang besar dari anggota rumah tangga pada aktivitas kerjanya membuat kontribusi pendapatan setiap anggota rumah tangga tersebut juga besar. Hal ini menunjukkan bahwa setiap anggota rumah tangga yang bekerja bersama-sama mencari nafkah untuk memenuhi kebutuhan hidup.…”
Section: Pendahuluanunclassified
“…Demi meningkatkan ekonomi keluarga khususnya keluarga yang tingkat ekonominya relatif rendah dan berpenghasilan tidak menentu, anggota rumah tangga lainnya ikut dilibatkan untuk membantu memenuhi kebutuhan rumah tangga dan mencapai kelentingan nafkah. Berdasarkan penelitian dari Djangaopa et al (2018), kontribusi pendapatan yang lebih besar bagi setiap anggota rumah tangga merupakan gambaran dari curahan waktu kerja setiap anggota rumah tangga pada aktivitas kerja tersebut. Perempuan pedagang sayuran memiliki potensi dalam peningkatan pendapatan yang nantinya akan meningkatkan kesejahteraan rumah tangga.…”
Section: Pendahuluanunclassified